Spending patterns of zakat recipients among students of higher education institution (HEIS) - Saidon, Rafeah; Khadijah Ab. Manan, Siti; Huda Sahari, Noorul; Adibah Ismail, Fadilah; ., . (International Journal of Engineering and Technology, 2018)
The disbursement of zakat to the recipients must be efficient and for the intended purpose. This is to ensure that the objectives of the Shariah in safeguarding the welfare of the ummah are achieved. As financial assistance by way of zakat would add more cash to the recipients (asnaf), there is a need to study the effectiveness of the cash they received as the absence of such information may contribute to the lack of evidence on the effectiveness of zakat in reducing the financial burden of the recipients. Therefore, this study examines the spending patterns of zakat recipients among University Technology MARA (UiTMâ€™s) students. This quantitative research used primary data gathered through a self-administered questionnaire. The sample of this study comprises of zakat recipients among students of UiTM Selangor. Questionnaires were distributed to a total of 400 respondents and the collected data were analysed descriptively. The findings showed that a sizeable portion of the studentsâ€™ spending was on necessities such as food, transport, shelter, clothing and learning materials. A considerable number of respondents spent on mobile phones and very few saved the money they received.Â